(untitled) (Research, Society and Development, 2022)
In 2019, the municipality of Cascavel-PR suffered its biggest dengue epidemic to date, and the present study aims to identify the epidemiological profile of confirmed and notified cases in this city, in order to assist it in the fight against this disease. The study uses a total sample of 3,795 cases. This work investigated notifications from the Notifiable Diseases Information System (SINAN) and DataSUS data, as well as the geographic distribution of confirmed cases using ArcGIS software. From the notifications, age, sex, pregnant or not, race, schooling, area of residence, clinical signs, non-specific laboratory findings, pre-existing diseases, results of IgM serology, Isolation, RT-PCR and Serotype were analyzed. of hospitalization, evolution of the case and its classification (dengue, dengue with warning signs and severe dengue). Descriptive statistics of absolute and relative frequency (for qualitative variables) and graphic representations were developed for the collected responses. In order to evaluate possible relationships between the hospitalization situation and the other observed qualitative factors, χ2 tests (Chi-square) or Fisher’s exact tests were performed, in the case of small sample. Most cases (52%) were women, 0.94% were pregnant and 1/4 of these required hospitalization. Four symptoms also stand out: fever, myalgia, headache and nausea, which were present in more than 50% of patients diagnosed with dengue. The research results show that the indexes present in the Municipality of Cascavel follow the pattern of the indexes presented throughout the State of Paraná-BR according to DataSUS.